2018
DOI: 10.1016/j.specom.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of spectral tilt measures for sentence prominence in speech—Effects of dimensionality and adverse noise conditions

Abstract: Linguistic prominence in speech is known to correlate with the acoustic measures of energy, F0, and duration. In contrast, the role of spectral tilt in the realization of prominence has remained more inconsistent between previous empirical investigations. This may be partially due to the lack of a standard method for quantifying spectral tilt or due to difficulties in estimating the acoustical source of spectral tilt, the glottal flow, from continuous speech. These issues have rendered interpretations and comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…We also evaluated the low/high energy ratio (reflecting spectral slope) which is a ratio of spectral energy levels between the low and high frequency ranges to investigate how this would be affected given the impact of mask-wearing on the speech spectrum. The low/high ratio using a 1000 Hz cut-off value (LH1000) has been used frequently in voice and speech research and has been shown to reflect voice quality 62,63 , vocal load 64 , sentence prominence in speech 66 , and the effects of language 67 . The low/high energy ratio between spectral areas below 1 Hz and between 1-8 kHz was measured for the /a/ vowel (averaged from three repeats) and RP23 using the long-term average spectra (LTAS) function in Praat.…”
mentioning
confidence: 99%
“…We also evaluated the low/high energy ratio (reflecting spectral slope) which is a ratio of spectral energy levels between the low and high frequency ranges to investigate how this would be affected given the impact of mask-wearing on the speech spectrum. The low/high ratio using a 1000 Hz cut-off value (LH1000) has been used frequently in voice and speech research and has been shown to reflect voice quality 62,63 , vocal load 64 , sentence prominence in speech 66 , and the effects of language 67 . The low/high energy ratio between spectral areas below 1 Hz and between 1-8 kHz was measured for the /a/ vowel (averaged from three repeats) and RP23 using the long-term average spectra (LTAS) function in Praat.…”
mentioning
confidence: 99%
“…In [ 16 , 59 ], speech in noisy conditions showed as a spectral energy boost between 0.5–1 kHz and 5 kHz when compared with the silent condition. There is high variance between different ways of measuring spectral tilt [ 60 ]; thus, here, spectral tilt was estimated using two separate methods.…”
Section: Methodsmentioning
confidence: 99%
“…In [17, 75] speech in noisy conditions showed as a spectral energy boost between 0.5–1 kHz and 5 kHz when compared to the silent condition. Different ways to measure spectral tilt show high variance [76], thus, in the current study, spectral tilt was estimated using two separate methods.…”
Section: Methodsmentioning
confidence: 99%